Pengaruh Penggunaan Strategi Giving Question and Getting Answer pada Pembelajaran Daring Biologi Via Whatsapp - Linda Yanti (ALVEOLI: Jurnal Pendidikan Biologi, 2020)
The strategy of using Giving Question and Getting Answer via Whatsapp need analysist of therelation in biology learning. The purpose of this study to determine whether there is influence of Whatsappof the strategy Giving Question and Getting Answers to biology online learning through Whatsapp. Thisresearch method uses a qualitative descriptive method. Data collection techniques using observation, interviews, and documentation. This study result indicated that learning that dares to use the Whatsapp application with a strategy of Providing Answers and Getting Questions can provide more fun learning so as toincrease student enthusiasm and activity. The conclusions obtained from this study use a strategy of AskingQuestions and Getting Answers that affect biology online learning through Whatsapp and can be an alternative in online biology learning through Whatsapp in conditions that do not support learning face-to-facelearning. Keywords : Giving Question and Getting Answer, Whatsapp, Online learning Penggunaan strategi Giving Question and Getting Answer via Whatsapp perlu dikaji terkaitpengaruhnya dalam pembelajaran biologi. Penelitian ini bertujuan untuk mengetahui ada tidaknyapengaruh penggunaan strategi Giving Question and Getting Answer pada pembelajaran daring biologi viaWhatsapp. Metode penelitian ini menggunakan metode deskriptif kualitatif. Data pada penelitian inidikumpulkan melalui observasi, wawancara, dan dokumentasi. Hasil yang diperoleh menunjukkan bahwaPembelajaran daring menggunakan aplikasi Whatsapp dengan strategi Giving Question and Getting Answer dapat memberikan pembelajaran yang lebih menyenangkan sehingga meningkatkan antusias dankeaktifan siswa. Kesimpulan yang diperoleh dari penelitian ini yaitu penggunaan strategi Giving Questionand Getting Answer berpengaruh terhadap pembelajaran daring biologi via Whatsapp dan bisa menjadialternatif dalam pembelajaran daring biologi via Whatsapp pada kondisi yang tidak memungkinkan untukdilakukannya pembelajaran tatap muka. Kata Kunci : Giving Question and Getting Answer, Whatsapp, Pembelajaran daring